Техніко-економічні аспекти застосування синхронно-асинхронної структури електрогенеруючих потужностей в енергосистемі України - Тітко, В.О. (Технічна електродинаміка, 2012)
Methodical means of definition of economic parameters of efficiency of application of synchronous-asynchronous structure electrogenerating capacities in a power supply system are developed. The technique is based on methods of dynamic programming for definition of an optimum policy of updating of the generating equipment. Researches of economic efficiency of simultaneous application of synchronous and asynchronous generators are carried out at their various ratio in the established capacity. It is shown, that the synchronous-asynchronous structure electrogenerating capacities essentially raises economic parameters, including predicted profit, expands borders of updating for maintenance of constant growth in time of the maximal profit.